Calico Joe - Grisham, John (Belfry Holdings, Inc., 2012)
In the summer of 1973 Joe Castle was the boy wonder of baseball, the greatest rookie anyone had ever seen. The kid from Calico Rock, Arkansas, dazzled Cubs fans as he hit home run after home run, politely tipping his hat to the crowd as he shattered all rookie records. Calico Joe quickly became the idol of every baseball fan in America, including Paul Tracey, the young son of a hard-partying and hard-throwing Mets pitcher. On the day tha Warren Tracey finally faced Calico Joe, Paul was in the stands, rooting for his idol but also for his dad. The Warren threw a fast-ball that would change their lives forever...
Keywords: Fiction; Sports - Baseball